Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan dan Loyalitas Pelanggan Restoran Chicken Geprek Ken Dedes - Ferawati, Dilla; Aminah, Mimin (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
Chicken Geprek Ken Dedes Restaurant is one of the small businesses in the midst of increasingly tight culinary MSME competition in Bogor. This restaurant needs to continuously increase customer satisfaction and loyalty to sustain business continuity. This study aimed to analyze customer characteristics, the effect of price and product quality on customer satisfaction and loyalty, the effect of customer satisfaction on customer loyalty, and the effect of customer satisfaction as a mediating variable. The sample of this research was 78 customers who were determined using a non-probability sampling method called voluntary sampling. Research data were analyzed using descriptive analysis and SEM-PLS methods. The results showed that price and product quality have positive and significant effect on customer satisfaction, but not significant on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty and has a full mediating effect.